Comparison of Ceftizoxime Plus Ampicillin-Sulbactam versus Gentamicin Plus Ampicillin-Sulbactam in the Prevention of Post-Transplant Early Bacterial Infections in Liver Transplant Recipients: A Randomized Controlled Trial - Shafiekhani, Mojtaba (Infect Drug Resist, 2020)
PURPOSE: In this study, we aimed to compare the efficacy of combined ceftizoxime with ampicillin-sulbactam versus combined gentamicin with ampicillin-sulbactam as prophylactic antibiotic regimen in preventing early bacterial PTIs in liver TX recipients at a referral center. PATIENTS AND METHODS: All patients older than 18 years who had undergone liver TX at Abu-Ali Sina transplantation center in Shiraz, Iran from July 2018 to April 2019 were included in this study. In a single-blinded manner, the participants randomly received either combined intravenous ceftizoxime plus ampicillin-sulbactam (ceftizoxime group) or gentamicin plus ampicillin-sulbactam (gentamicin group) as prophylactic antibiotic regimen before the incision of the surgery, which was continued for 48 hrs after liver Tx. The rate and type of bacterial infections, length of hospital and intensive care unit (ICU) stay, mortality rate, and kidney function were assessed during 1 month following liver TX in the two groups. RESULTS: Two hundred and thirty patients were divided into two groups. One patient in the gentamicin group and five in the ceftizoxime group were excluded due to emergency exploratory laparotomy within the first 3 days after transplantation. The rate of bacterial infections during the first month after transplantation was 25.4%. This rate was significantly lower in the gentamicin group (13.16%) in comparison to the ceftizoxime group (38.18%) (P value<0.01), based on the univariate logistic regression analysis. Length of ICU and hospital stay and also mortality rate were significantly lower in the gentamicin group (P value <0.01). There was no significant difference regarding kidney function between the two groups (P value = 0.16). CONCLUSION: Our results suggested that gentamicin can be considered as a promising agent in prophylactic antibiotic regimen for patients undergoing liver TX. TRIAL REGISTRATION: The study was registered at the Iranian Registry of Clinical Trials (IRCT20120731010453N2; http://www.irct.ir/).